2004
DOI: 10.1074/jbc.m408934200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Topoisomerase IV C-terminal Domain

Abstract: Bacteria possess two closely related yet functionally distinct essential type IIA topoisomerases (Topos). DNA gyrase supports replication and transcription with its unique supercoiling activity, whereas Topo IV preferentially relaxes (؉) supercoils and is a decatenating enzyme required for chromosome segregation. Here we report the crystal structure of the C-terminal domain of Topo IV ParC subunit (ParC-CTD) from Bacillus stearothermophilus and provide a structure-based explanation for how Topo IV and DNA gyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 54 publications
0
43
1
1
Order By: Relevance
“…One is the presence of a GyrA-box, QRRGGKG (19), and the other is the fact that the ParC CTD possesses only five blades. However, some ParC CTDs possess six blades (14,15). Thus, the GyrA-box turns out to be the only motif that is present in GyrA CTDs, but not in ParC CTDs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One is the presence of a GyrA-box, QRRGGKG (19), and the other is the fact that the ParC CTD possesses only five blades. However, some ParC CTDs possess six blades (14,15). Thus, the GyrA-box turns out to be the only motif that is present in GyrA CTDs, but not in ParC CTDs.…”
Section: Resultsmentioning
confidence: 99%
“…Alterations of the GyrA-box-Structural studies have revealed two differences between E. coli GyrA and E. coli ParC CTDs (12)(13)(14)(15)(16). One is the presence of a GyrA-box, QRRGGKG (19), and the other is the fact that the ParC CTD possesses only five blades.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The function of topo II's C-terminal region is not well understood, except that it is implicated in the regulation of topo II (25). Recent studies on two other closely related type IIA topos, DNA gyrase and topo IV, suggest that their C-terminal domains bind and bend DNA to correctly position substrate DNA for the enzymatic reaction (26,27). Although RHL1 does not have significant homology to the C terminus of DNA gyrase or topo IV, it is possible that RHL1 performs a similar function.…”
Section: Hyp7 Is Essential For Successive Endocycles Beyond 8cmentioning
confidence: 99%